2010
DOI: 10.1021/jz100838c
|View full text |Cite
|
Sign up to set email alerts
|

Direct Information on Structure and Energetic Features of Cu+−Xe Species Formed in MFI-Type Zeolite at Room Temperature

Abstract: The interacted species of Xe with metal ions that are stable at room temperature are not known and are a subject of interest for fundamental chemistry. We have experimentally found a new and stable Xe species, XeCu þ , which was formed at room temperature in a copper ion-exchanged MFI-type zeolite. The presence of a prominent interaction between Cu þ in MFI and Xe, which has a covalent nature, was for the first time evidenced from experimental in situ synchrotron X-ray absorption fine structure and heat of ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 65 publications
2
36
0
Order By: Relevance
“…larger than 3.58 Å, the sum of oxygen and xenon vdW radii, and therefore suggesting for Xe a gaseous-like situation. These results represent an improvement with respect to previous work by Torigoe et al 30 who studied the structure of Xe inside a Cu-MFI by XAS and theoretical calculations with the cluster approach. They obtained precious information on Cu-Xe distances and local Xe structure, but the experimental Xe positions in the unit cell (Table 4) could be obtained only by XRD.…”
Section: The Behavior Of Xe Inside Mfi Channelssupporting
confidence: 55%
See 1 more Smart Citation
“…larger than 3.58 Å, the sum of oxygen and xenon vdW radii, and therefore suggesting for Xe a gaseous-like situation. These results represent an improvement with respect to previous work by Torigoe et al 30 who studied the structure of Xe inside a Cu-MFI by XAS and theoretical calculations with the cluster approach. They obtained precious information on Cu-Xe distances and local Xe structure, but the experimental Xe positions in the unit cell (Table 4) could be obtained only by XRD.…”
Section: The Behavior Of Xe Inside Mfi Channelssupporting
confidence: 55%
“…The Xe-MFI system is chosen to serve as an interesting example of an activespectator interaction, which cannot be rationalized without structural information about the location of Xe inside zeolite channels. To the best of our knowledge, only XAS and computational studies on Xe inside MFI are available, 30 while XRD investigations are not yet reported. Very recently, adsorption/ desorption Xe in MOFs was studied with the aim of reducing Xe purification costs.…”
Section: Introductionmentioning
confidence: 99%
“…Following our previous studies, periodic ZSM-5 structure was modelled using an aluminium-free ZSM-5 cluster (Si 92 O 151 H 66 ). [59][60][61][62][63][64][65] Si atoms within a ten-membered ring of ZSM-5 zeolite were then substituted by Al atoms, where the number of the Al atoms is m. The ZSM-5 cavity containing the substituted Al atoms is denoted as ZSM-5(Al m ). Using the nitesize model, the initial structures were constructed by placing an Ag n cluster into a ten-membered ring of ZSM-5(Al m ) zeolite.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, our studies confirmed that this B3LYP-optimized MFI zeolite model comprised of 10-MR in cavities reproduced well the experimentally observed data. [12][13][14]22,[24][25][26][27][28][29][30][31] Taking our previous studies into consideration, we used the M7 site for the Al substitution position; 32 and we defined the Al configuration as the [M7-S2] arrangement. [12][13][14]30 To optimize fully the larger MFI geometry with a 10-MR cavity, we used the 6-311G(d) basis set for the zinc atom and the 6-31G (d) basis set for the Al atom, as well as four O atoms that were connected to the substituted Al atom.…”
Section: Computational Methodology (Calculation Method)mentioning
confidence: 99%